A Review on Influence of Spray Drying Process Parameters on the Production of Medicinal Plant Powders - Gallo, Loreana; Bucalá, Verónica (Current Drug Discovery Technologies, 2019)
Medicinal plants are used by 80% of the world population as primary health care and the phytomedicine market is growing exponentially. Currently, the production of phytopharmaceuticals with proper efficacy, safety and consistent quality constitutes a relevant challenge. The dried dosage forms of medicinal plants are preferred than liquid presentations because of their higher stability. The spray drying technology is the most employed process to produce dried extracts from medicinal plant liquid extracts. These powders need to meet certain physicochemical (e.g., moisture content, hygroscopicity, particle size, density, the concentration of active ingredients) and mechanical (e.g., flowability and compressibility) properties to be used in a solid pharmaceutical form. In addition, high process yields and good powder quality can be obtained by selecting suitable process parameters: spray drying operating conditions and type/concentration of carriers (drying coadjuvants). The optimal process parameters are strongly affected by the chemical nature of the medicinal plant extract. This review aims to give a general guide to understand the effect of the process parameters on the product properties and process yield. This guideline could help practitioners and researchers to initially select the levels of the process variables to decrease the time and cost of the development stage of medicinal plants powders.
Keywords: operating conditions